Highlighting smart city mirages in public perceptions: A Twitter sentiment analysis of four African smart city projects. (November 2022) - Arku, Robert Nutifafa; Buttazzoni, Adrian; Agyapon-Ntra, Kwadwo; Bandauko, Elmond
Abstract: 'Smart cities' strategies are often promoted as a panacea to existing urban planning issues such as local economic development, public safety, traffic congestion, and infrastructure maintenance. While these initiatives continue to be increasingly sought out and publicly promoted by governments across the globe, little is known about the influence of smart city branding campaigns on public perceptions of such projects. To explore this dynamic, we conducted a sentiment analysis of tweets regarding four smart city projects in Africa using the NRC Emotion Lexicon. The analysis revealed strong and consistent positive associations with words annotated with the emotions of Anticipation, Trust, and Joy. Based on these cross-case trends, we speculate that given their underwhelming outputs, the larger smart city agenda and its accompanying strategic positive framing have contrived a potentially pervasive and illusionary sentiment of "smart city mirages" among the public consciousness. Highlights: Investigating public perceptions of selected smart city case studies in Africa. A sentiment analysis of tweets using the NRC Emotion Lexicon. Strong positive emotions are consistently associated with the smart city projects. Promotion of smart cities potential create "smart city mirages" in public perceptions